Designing and Manufacturing the Cryoconcentration Equipment (Cold Concentrator) and Apply It to Concentrate a High-quality Product from Dragon (Hylocereus) Fruit Juice - Chau, Thanh Tuan; Do, Thuy Khanh Linh; Nguyen, Tan Dung (Journal of Technical Education Science, 2023)
Dragon (Hylocereus) fruit juice is a nutrient-rich solution that can be easily infected by environmental microorganisms, causing fermentation and spoilage, leading to a short preservation time. Fruits and other food Have been preserved by methods – cold storage, concentration, or vacuum concentration – that are energy-intensive or lead to a quick reduction in the product’s quality. The cryoconcentration method used in dragon fruit is one of the reasonable ways to preserve vitamins, bioactive compounds, and nutritional ingredients. However, there is no widespread usage or production of equipment specifically designed for a cold concentrator. This study aims to calculate, design, and manufacture the concentrator equipment named CCE-03. The manufactured equipment has a capacity of 5L per batch, with a -10 to -35 °C concentration ambient, a concentration-time from 1.5 to 6 hours, a defrosting temperature of 10 to 25 °C, and is controlled by an automatic measuring device operated through a computer, and works stably. The concentrating process takes 1.6 hours; the energy cost is 0.48kWh/L of the product. The product concentration is 46.6%, and the loss of vitamin C content is 11.3%. The concentrated dragon juice is high-quality.